EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN KECERDASAN EMOSIONAL SISWA KELAS XI IPA SMA IP YAKIN JAKARTA TAHUN AJARAN 2016/2017 - Amir Erwin; Wahidahtun NA (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2018)
The purpose of this research is toproduce group counseling services tohelp students improve theiremotional intelligence with researchsubjects are senior high schoolstudents of XI Science Class at IPYAKIN School Jakarta. Thisresearch used a quantitativeapproach with a quasi-experimentalmethod using Non EquivalentControl Group Design. Technique ofsampling using probability samplingis cluster sampling. Population was81 students and sample was 53students which divided into 2 (two)groups: 26 students in theexperimental group and 27 studentsin the control group. Technique ofcollection data using questionnaire,40 of 73 items of questionnaire werevalid and spreaded to researchrespondents. Technique of dataanalysis used is T-Test. T-Test resultsof the experimental group was tcount=2,401 and ttabel= 2,0086 (df= 26-26-2=50; α=0,05). Final result of thisresearch as tcount > ttabel is 2,401 >2,0086. Hereby declared that thenihil hypothesis (H0) stated “There isno effectiveness of guidance groupservice to improve EmotionalIntelligence to Senior High SchoolStudents of XI Science Class at IPYAKIN School Jakarta” is rejected.Whereas the alternative hypothesis(H1) stated “There is effectiveness ofguidance group service to improveEmotional Intelligence to SeniorHigh School Students of XI ScienceClass at IP YAKIN School Jakarta”is accepted